New Insights in Microplastic Cellular Uptake Through a Cell-Based Organotypic Rainbow-Trout (Oncorhynchus mykiss) Intestinal Platform - Nicole Verdile; Nico Cattaneo; Federica Camin; Matteo Zarantoniello; Federico Conti; Gloriana Cardinaletti; Tiziana A. L. Brevini; Ike Olivotto; Fulvio Gandolfi (Cells)
Microplastics (MPs) in fish can cross the intestinal barrier and are often bioaccumulated in several tissues, causing adverse effects. While the impacts of MPs on fish are well documented, the mechanisms of their cellular internalization remain unclear. A rainbow-trout (Oncorhynchus mykiss) intestinal platform, comprising proximal and distal intestinal epithelial cells cultured on an Alvetex scaffold, was exposed to 50 mg/L of MPs (size 1–5 µm) for 2, 4, and 6 h. MP uptake was faster in RTpi-MI compared to RTdi-MI. Exposure to microplastics compromised the cellular barrier integrity by disrupting the tight-junction protein zonula occludens-1, inducing significant decreases in the transepithelial-electrical-resistance (TEER) values. Consequently, MPs were internalized by cultured epithelial cells and fibroblasts. The expression of genes related to endocytosis (cltca, cav1), macropinocytosis (rac1), and tight junctions’ formation (oclna, cldn3a, ZO-1) was analyzed. No significant differences were observed in cltca, oclna, and cldn3a expression, while an upregulation of cav1, rac1, and ZO-1 genes was detected, suggesting macropinocytosis as the route of internalization, since also cav1 and ZO-1 are indirectly related to this mechanism. The obtained results are consistent with data previously reported in vivo, confirming its validity for identifying MP internalization pathways. This could help to develop strategies to mitigate MP absorption through ingestion.